Actor's skills in pantomime theater performances (Al-Academy, 2022)
The art of pantomime mime is one of the arts that has taken a wide space in theater performances, and because it is one of the spectacle shows that relies on an acting performance that is unique from the traditional acting performance, because of the peculiarity of pantomime art in that it is a silent performance that assumes the clarity of meaning, and for the purpose of clarifying the actor’s work in such kind of performances, the art of pantomime must be We have to know the skills that the actor can possess in order to produce a silent show that has the elements of a successful presentation, so there was a need to study the skills of the actor in this type of acting performance. The researchers divided this study into an introduction in which they dealt with the research problem formulated in the following question: What is The performance skills that the actor has to master? Then the research objective and the definition of the study term. As for the theoretical foundation, it included two topics: the first topic (the development of the art of the pantomime) and the second topic (the technical skills of the representative of the pantomime). In 2006. Then the two researchers reached a set of results, including: The skill of completing each theatrical act before starting another theatrical act must be present with the actor so that the spectator does not confuse the description of the forms, the event and the story. Then a summary and sources of research in English.